Delayed recognition of fatal invasive meningococcal disease in adults. Issue 3 (28th June 2016) - Nagel, Frederick W.; Ezeoke, Ifeoma; Antwi, Mike; Del Rosso, Paula E.; Dorsinville, Marie; Isaac, Beth M.; Hayden, Althea; Hoffman, Robert S.; Weingart, Scott D.; Weiss, Don
Abstract : Introduction: Invasive meningococcal disease can be difficult to detect early in its course when patients may appear well and the severity of their illness is obscured by non-specific complaints. Case presentation: We report five cases of meningococcal sepsis in adult patients who presented to an emergency department early in the course of their disease, but whose severity of illness was not recognized. Conclusion: Suspicion of meningococcal sepsis should be heightened in the setting of hypotension, tachycardia, elevated shock index, leukopaenia with left shift, thrombocytopaenia and hypokalaemia, prompting early sepsis care.